PRINCIPLES OF PREVENTIVE THERAPY IN PREGNANT WOMEN WITH METABOLIC SYNDROME - E. B. Perederyaeva; T. B. Pshenichnikova; A. D. Makatsariya (Акушерство, гинекология и репродукция, 2016)
Metabolic syndrome is widespread among women of reproductive age. Metabolic syndrome is associated with at higher risk of developing various obstetric complications. The hereditary or acquired forms of thrombophilia may play an important role in impaired invasion cytotrophoblast and impaired placental development. It may lead to fetal loss syndrome, pre-eclampsia, intrauterine growth retardation and other obstetric complications in women with metabolic syndrome The earlier antithrombotic prophylaxis is initiated, the better the outcome of pregnancy will be.